2012
DOI: 10.1002/jez.1752
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Localization of Two Types of Fast Skeletal Myosin Heavy Chain Genes From Black Tiger and Pacific White Shrimps

Abstract: The physiology and biochemistry of skeletal muscles in shrimps have been poorly understood compared with those from vertebrates. The present study was conducted focusing on myosin, the major protein in skeletal muscle, from adult specimens of black tiger Penaeus monodon and Pacific white Penaeus vannamei shrimps. Two genes encoding myosin heavy chain (MHC), a large subunit of the myosin molecule, were cloned from abdominal fast skeletal muscle and defined as MHCa and MHCb according to our previous study on kur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…It has been confirmed that MHC1 and MHC2 transcripts are localized in adult abdominal muscle of the three shrimp species by in situ hybridization and Northern blot analysis, whereas both transcripts were not detected in adult pleopod muscle (Koyama et al, ). In this study, we cloned MHC s encoding C‐terminal sequences from adult pleopod muscle of the three shrimps by using a degenerate forward primer and GeneRacer 3′ Primer.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…It has been confirmed that MHC1 and MHC2 transcripts are localized in adult abdominal muscle of the three shrimp species by in situ hybridization and Northern blot analysis, whereas both transcripts were not detected in adult pleopod muscle (Koyama et al, ). In this study, we cloned MHC s encoding C‐terminal sequences from adult pleopod muscle of the three shrimps by using a degenerate forward primer and GeneRacer 3′ Primer.…”
Section: Discussionmentioning
confidence: 77%
“…CODEHOP (COnsensus‐DEgenerate Hybrid Oligonucleotide Primers) (Rose et al, ) was used to design degenerate primer F (Table ) based on the deduced amino acid sequences of MHC from fruit fly Drosophila melanogaster (DDBJ/EMBL/GenBank accession number AAA28686) and American lobster fast‐ (U03091) and S 1 slow twitch‐type (AY232598) MHCs. This primer has been demonstrated to amplify DNA fragments encoding MHCs from abdominal muscle of kuruma, black tiger, and Pacific white shrimps as reported previously (Koyama et al, ).…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations